IMPROVEMENT OF STUDENTSâ SCIENTIFIC WRITING OF BIOLOGY EDUCATION OF SEBELAS MARET UNIVERSITY THROUGH READING PROJECT BASED LEARNING - Probosari, R. M. (Jurnal Pendidikan IPA Indonesia, 2015)
This study examined how studentsâ scientific writing skills changed over as they participated in the Reading Project Based Learning (RPjBL) model. This action research was conducted by Biology Teacher of Education Program Faculty of Teacher Training and Education in SebelasMaret University. The results show that the scientificwriting level increased on the last writing activities. It was suggested that RPjBL could have a positive impact on studentsâ scientific writing. Students who experienced the RPjBL emphasized the sentences reflecting the application and used high cognitive level sentences.Â  Â